PERAN ENTERPRISE RESOURCE PLANNING EPICOR DALAM MENINGKATKAN PENGELOLAAN UTANG PADA PT. XYZ - Istna Fibriyadi; Hesti Rian; Amelia Ananda; Desi Anggraini (DIVERSITY: Journal of Multi Science Linearity, 2024)
This study aims to examine how debt management is implemented and to analyze the role of ERP (Enterprise Resource Planning) Epicor in improving debt management at PT XYZ. Debt management is a crucial aspect in maintaining the financial stability of a company and ensuring smooth relationships with suppliers. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The results of the study show that each division in the company, including Sales, Production Planning and Inventory Control (PPIC), Purchasing, Warehouse, and Finance, plays an important role in the emergence of trade payables. The use of ERP Epicor has proven to facilitate the process of recording debt invoices, monitoring payable status, and scheduling payments systematically and efficiently.